A Positive Feedback Loop of Hippo- and c-Jun-Amino-Terminal Kinase Signaling Pathways Regulates Amyloid-Beta-Mediated Neurodegeneration - Irwin, Madison; Tare, Meghana; Singh, Aditi; Puli, Oorvashi Roy; Gogia, Neha; Riccetti, Matthew; Deshpande, Prajakta; Kango-Singh, Madhuri; Singh, Amit (Frontiers in Cell and Developmental Biology, 2020)
Alzheimer’s disease (AD, OMIM: 104300) is an age-related disorder that affects millions of people. One of the underlying causes of AD is generation of hydrophobic amyloid-beta 42 (Aβ42) peptides that accumulate to form amyloid plaques. These plaques induce oxidative stress and aberrant signaling, which result in the death of neurons and other pathologies linked to neurodegeneration. We have developed a Drosophila eye model of AD by targeted misexpression of human Aβ42 in the differentiating retinal neurons, where an accumulation of Aβ42 triggers a characteristic neurodegenerative phenotype. In a forward deficiency screen to look for genetic modifiers, we identified a molecularly defined deficiency, which suppresses Aβ42 mediated neurodegeneration. This deficiency uncovers hippo (hpo) gene, a member of evolutionarily conserved Hippo signaling pathway that regulates growth. Activation of Hippo signaling causes cell death whereas downregulation of Hippo signaling triggers cell proliferation. We found that Hippo signaling is activated in Aβ42-mediated neurodegeneration. Downregulation of Hippo signaling rescues the Aβ42-mediated neurodegeneration whereas upregulation of Hippo signaling enhances the Aβ42-mediated neurodegeneration phenotypes. It is known that c Jun-amino-terminal Kinase (JNK) signaling pathway is upregulated in AD. We found that activation of JNK signaling enhances the Aβ42-mediated neurodegeneration whereas downregulation of JNK signaling rescues the Aβ42-mediated neurodegeneration. We tested the nature of interactions between Hippo- and JNK- signaling in Aβ42 mediated neurodegeneration using genetic epistasis approach. Our data suggests that Hippo signaling and JNK signaling, two independent signaling pathways act synergistically upon accumulation of Aβ42 plaques to trigger cell death. Our studies demonstrate a novel role of Hippo signaling pathway in Aβ42 mediated neurodegeneration.